ANALISIS PENERAPAN MANAJEMEN PAJAK PENGHASILAN USAHA MIKRO KECIL MENENGAH - Gien Agustinawansari; Trisnawati Rahayu Rahayu; YP Supardiyono (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
Every business actor will be faced with tax regulations. Many things related to taxation are regulated by the government. This tax regulation applies to individual taxpayers and corporate taxpayers, whether running a business or not owning a business. Taxpayers can use the loopholes in the tax regulations to manage the taxes they are obligated to pay. Utilization of loopholes in tax regulations by taxpayers is not carried out by violating tax regulations. The goal to be achieved by taxpayers is to pay the lowest possible tax. Tax management that can be carried out by taxpayers related to income tax includes: selecting the type of taxpayer, carrying out bookkeeping or recording, selecting the size of the business, selecting the preparation method, selecting the legal form. The right selection made by the Taxpayer can result in a lower income tax liability. Keywords: management, small business, taxes, bookkeeping, recording